THE MODERNIZATION OF MADRASAH IN THE PERSPECTIVE OF A. MALIK FADJAR - Muh Idris; Evra Willya (Academic Bright Collaboration, 2026)
This study aims to explore and deeply analyze the intellectual construction of A. Malik Fadjar regarding the modernization of the madrasah as an effort toward inclusive and progressive Islamic educational reconstruction in Indonesia. Specifically, the study identifies his strategic steps in eliminating the intellectual dichotomy and reforming institutional management in response to the challenges of globalization. This study is a qualitative research employing a library research design with a focus on biographical and intellectual study (studi tokoh). Since the primary object of investigation is the intellectual thought of A. Malik Fadjar regarding the modernization of the madrasah, the approach utilized is the social history of Islamic educational thinking. This approach was selected because the researcher intends not only to dissect the texts literally but also to explore the dialectic between the figure's thoughts and the surrounding social, political, and cultural contexts during the inception of those ideas. The results demonstrate that madrasah modernization, from A. Malik Fadjar's perspective, is a paradigmatic transformation rooted in the concept of Tawhid as the convergence point for integrating science (dhikr) and technology (fikr). He positioned the madrasah no longer as a